2021
DOI: 10.3389/fneur.2021.702088
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal CT Imaging Characteristics in Predicting Prognosis of Wake-Up Stroke

Abstract: Background: Multimodal CT imaging can evaluate cerebral hemodynamics and stroke etiology, playing an important role in predicting prognosis. This study aimed to summarize the comprehensive image characteristics of wake-up stroke (WUS), and to explore its value in prognostication.Methods: WUS patients with anterior circulation large vessel occlusion were recruited into this prospective study. According to the 90-day modified Rankin Scale (mRS), all patients were divided into good outcome (mRS 0–2) or bad (mRS 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our meta-analysis revealed a clear association of decreasing ASPECTS with odds of poor functional outcomes regardless of the RT received. This is in line with the previous studies that found that decreased ASPECTS are associated with worse functional outcomes [ 16 , 19 , 22 , 33 , 35 , 38 ]. Despite the study design and cohort size, most of the included studies in this meta-analysis found a significant relationship between poor functional outcomes and ASPECTS cut-off points of 6 [ 27 , 30 , 36 , 37 , 38 ], 7 [ 24 , 25 , 26 , 34 , 38 ] and 8 [ 6 , 23 , 29 , 31 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our meta-analysis revealed a clear association of decreasing ASPECTS with odds of poor functional outcomes regardless of the RT received. This is in line with the previous studies that found that decreased ASPECTS are associated with worse functional outcomes [ 16 , 19 , 22 , 33 , 35 , 38 ]. Despite the study design and cohort size, most of the included studies in this meta-analysis found a significant relationship between poor functional outcomes and ASPECTS cut-off points of 6 [ 27 , 30 , 36 , 37 , 38 ], 7 [ 24 , 25 , 26 , 34 , 38 ] and 8 [ 6 , 23 , 29 , 31 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…The 6 studies, comprising 735 patients, included in the meta-analysis demonstrated that there was a significant association of increasing ASPECTS with poor functional outcomes at 90 days (SMD = −1.15; 95% CI −1.77–−0.52; p < 0.0001) ( Figure 3 ) [ 16 , 19 , 22 , 33 , 35 , 38 ]. Moderate to considerable heterogeneity was found between the studies (I 2 = 93.1%, p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations